Custom design of a hanging cooling water power generating system applied to a Sensitive cooling water discharge weir in a seaside power plant : A challenging energy scheme - Chuan, Min Tian; Mohd Narzam, Jaffar; Harunal Rejan, Ramji; Mohammad Omar, Abdullah (Elsevier Ltd., 2015)
In this study, an innovative design of hydro-electricity system was applied to an unconventional site in an attempt to generate electricity from the exhaust cooling water of a coal-fired power plant. Inspired by the idea of micro hydro, present study can be considered new in three aspects: design, resource and site. This system was hung at a cooling water discharge weir, where all sorts of civil work were prohibited and sea water was used as the cooling water. It was designed and fabricated in the university's mechanical workshop and transported to the site for installation. The system was then put into proof run for a three-month period and achieved some success. Due to safety reasons, on-site testing was prohibited by the power plant authority. Hence, most data was acquired from the proof run. The driving system efficiency was tested in the range of 25% and 45% experimentally while modeling results came close to experimental results. Payback period for the system is estimated to be about 4.23 years. Result obtained validates the feasibility of the overall design under the sensitive site application.